STUDI LITERATUR : MEDIA AUGMENTED REALITY DALAM MENINGKATKAN PEMAHAMAN BANGUN RUANG DI SEKOLAH DASAR - anti, novi (Tunas Nusantara, 2024)
Learning media is needed to be able to help students achieve changes in behavior, support their imagination in actively participating in class, and foster enthusiasm for learning. The aim of this research is to describe the meaning of learning media, describe augmented reality media, describe spatial structures, and describe the role of augmented reality media in spatial materials in elementary schools. The role of augmented reality media in increasing understanding of spatial structures in elementary schools is important because A can help students understand the material more easily and make learning more interesting and motivating. This research was carried out using library research, so the method used was the library study research method. There are stages in this research to describe data, namely through collecting scientific articles, books and relevant sources in the years 2013-2023 which are then analyzed. The result of this research are : 1) Learning media is one of the factors that plays an important role in the learning and teaching process; 2) Augmented Reality (AR) media as a technology that combnes two or three-dimensional objects in real time; 3) a geometric shape is a type of reguler spatial object that has edges, sides and corner points; and 4) Augmented Reality (AR) media makes a positive contribution in increasing understanding of spatial structures in elementary schools.Keyword :Â Augmented Reality, Geometry, Learning Media